Pemberdayaan Masyarakat Desa Bayongbong Kabupaten Garut - Fitriani, Fingki; Hikmawati, Ikeu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This empowerment aims to increase the role of village government in improving community welfare and reducing inhibiting factors. This research uses qualitative methods in the form of descriptive research. The selection of informants was carried out purposively, where data was collected using interviews, observation and documentation studies. Data is collected from various sources until sufficient data is obtained. The data obtained is then analyzed interactively. Community empowerment in Bayongbong Village, Garut Regency, which is carried out by the village government, is carried out through human development, business development, environmental development and institutional development activities, however, in community empowerment there are still various obstacles, including socialization that has not been maximized, a community mindset that finds it difficult to take innovation for granted. , new ideas and knowledge, limited budgets and the existence of several government regulations which are considered to hinder community empowerment because they are not in accordance with regional needs and potential, so it is necessary to increase and strengthen the government's role in community empowerment which must be further optimized, village government officials to increase cooperation well and fostering harmonious relationships both with community institutions and with the community, it is necessary to pay attention to the obstacles that hinder the community empowerment process so that they can be used as a reference in the next program.